Atomic-level separation of thiolate-protected metal clusters. Issue 15 (24th March 2020) - Negishi, Yuichi; Hashimoto, Sayaka; Ebina, Ayano; Hamada, Kota; Hossain, Sakiat; Kawawaki, Tokuhisa
Abstract : This review summarizes previous studies on high-resolution separation of Au n (SR) m clusters for better understanding the utility of each separation technique. Abstract : Fine metal clusters have attracted much attention from the viewpoints of both basic and applied science for many years because of their unique physical/chemical properties and functions, which differ from those of bulk metals. Among these materials, thiolate (SR)-protected gold clusters (Au n (SR) m clusters) have been the most studied metal clusters since 2000 because of their ease of synthesis and handling. However, in the early 2000s, it was not easy to isolate these metal clusters. Therefore, high-resolution separation methods were explored, and several atomic-level separation methods, including polyacrylamide gel electrophoresis (PAGE), high-performance liquid chromatography (HPLC), and thin-layer chromatography (TLC), were successively established. These techniques have made it possible to isolate a series of Au n (SR) m clusters, and much knowledge has been obtained on the correlation between the chemical composition and fundamental properties such as the stability, electronic structure, and physical properties of Au n (SR) m clusters. In addition, these high-resolution separation techniques are now also frequently used to evaluate the distribution of the product and to track the reaction process. In this way, high-resolution separation techniques have played an essential role in the study of Au n (SR) m clusters. However, only a few reviews have focused on this work. This review focuses on PAGE, HPLC, and TLC separation techniques, which offer high resolution and repeatability, and summarizes previous studies on the high-resolution separation of Au n (SR) m and related clusters with the purpose of promoting a better understanding of the features and the utility of these techniques.